Peranan Pemangku Kepentingan dalam Pengelolaan Berkelanjutan BUMDes Barokah Desa Tugu Utara, Kecamatan Cisarua, Kabupaten Bogor - yuyun yunardi; Akhmad Fauzi; Sri Mulatsih (P4W LPPM IPB, 2019)
The Role of Stakeholders in Sustainable Management of BUMDes Barokah Tugu Utara Village, Cisarua District, Bogor Regency The establishment of village-owned business entity (BUMDes) is a mandate of the Village Law as an effort to encourage or stimulate rural economy, as well as an effort to increase village income. The village of Tugu Utara has formed a BUMDes institution to utilize its very abundant spring water sources. Utilization of spring water resources, which is a common resource, must be managed properly and involve all stakeholders so that clean water sources could be maintained in a sustainable manner. This study aims to investigate the role and influence of each stakeholder, as well as patterns of interaction between them as an effort to improve the management of BUMDes in Tugu Utara Village. The method used is Mactor Analysis. Results of analysis show that the stakeholder with the highest influence is Perhutani, meanwhile the stakeholder with the highest dependency is the manager of BUMDes. Good interaction is given by the head of village, the manager of the BUMDes, and Save Puncak Consortium of IPB University. Negative responses are given by stakeholders from PT Lintas Daya Kreasi and PT Sumber Sari Bumi Pakuan. Collaborative planning is needed among stakeholders in order to build a shared understanding of spring water governance.